ACCOUNTING INFORMATION QUALITY ON MICRO, SMALL, AND MEDIUM ENTERPRISE, A NECESSITY? - Yanuar Ramadhan (Jurnal ASET (Akuntansi Riset), 2022)
This study aims to explore the effect of the relationship between accounting information systems quality on accounting information quality in MSME companies. The method of collecting data through distributing questionnaires related to the variables studied, namely Accounting Information Systems Quality and Accounting Information Quality. The type of data used in this study is primary data with this questionnaire is causality. The inferential analysis method used is simple linear regression which will test between hypothesised variables (explanatory research) and aims to determine the effect of variables by analysing factors related to Accounting Information Systems Quality and Accounting Information Quality. The results showed that Accounting Information Systems Quality affects Accounting Information Quality. Research shows the importance of accounting information systems quality that will produce accounting information quality. The results of this study are very important for companies, especially for MSMEs, that accounting information quality will help entrepreneurs in making the right decisions. This research is concluded based on MSME respondents who answered the questionnaire, which does not include MSMEs in a broader scope and has not been arranged based on their respective classifications, namely micro, small, or medium.